Angiopoietin‐2 as a predictor of acute kidney injury in critically ill patients and association with ARDS. Issue 4 (17th January 2019) - Araújo, Camila Barbosa; de Oliveira Neves, Fernanda Macedo; de Freitas, Daniele Ferreira; Arruda, Bianca Fernandes Távora; de Macêdo Filho, Leonardo José Monteiro; Salles, Vivian Brito; Meneses, Gdayllon Cavalcante; Martins, Alice Maria Costa; Libório, Alexandre Braga
ABSTRACT: Background and objective: Angiopoietin‐2 (AGPT2) has been proposed as a key mediator of organ dysfunction, mainly in acute respiratory distress syndrome (ARDS). It has also been associated with acute kidney injury (AKI). We aimed to investigate the role of AGPT2 in patients with and without ARDS. Methods: In a cohort study with critically ill patients, AGPT1 and AGPT2 were assayed in plasma collected within the first 24 h after admission to intensive care unit (ICU). Severe AKI and the need for dialysis were outcome measures from comparative analysis with clinical characteristics useful for AKI risk stratification. Results: Among 283 patients (50.2% males), 109 (38.5%) had ARDS. AGPT2 levels at admission were higher in patients with ARDS. Although overall AGPT2 and AGPT2/AGPT1 levels were associated with severe AKI, this association was not significant in patients without ARDS; however, it remained strongly significant in ARDS patients. In patients without ARDS, AGPT2 showed only a weak discriminatory capacity to predict severe AKI (area under the curve (AUC): 0.64 vs 0.81 in the ARDS group). The continuous net reclassification improvement (NRI) in the ARDS group resulting from AGPT2 inclusion was 64.1% ( P < 0.001) and the integrated discrimination improvement (IDI) index was 0.057 ( P = 0.003). There was no significant difference in NRI in the no‐ARDS group. Conclusion: AGPT2 and AGPT2/AGPT1 ratio are associated with severe AKI and there was only a need of renal replacement therapy (RRT) in patients with or at risk of ARDS, not in other critically ill patients. Adding AGPT2 to a clinical model resulted in a significant improvement in the capacity to predict severe AKI specifically in ARDS patients. Abstract : Angiopoietin‐2 (AGPT2) is a known acute respiratory distress syndrome (ARDS) biomarker and its use has been recently proposed for acute kidney injury (AKI). We demonstrated that AGPT2 is associated with AKI only in patients with or developing ARDS. Adding AGPT2 to a clinical model results in significant improvement in the capacity to predict severe AKI in patients with ARDS.